Our Lady of Assumption Church at Kandivli village - Mumbai Archive Project Team (Jio Institute, 2024)
The East Indian community has a significant population in Kandivli and its suburbs. Native Catholics established a church of the same name at Magathane around half a mile east of the present Kandivli Railway station in 1630. This church was the precursor to the present Our Lady of Assumption Church at Kandivli village.